Norma constitucional de competência: vetor de definição e interpretação do precedente judicial no processo tributário - Mattos Júnior, José Luiz Franco de Moura (2017)
The New Civil Procedure Code (Law nº 13.105, of March 16th, 2015) appears to some theorists, as an important solution in the judicial process, to the instability resulting from the exegetical controversies on tax regulations. Some processualists present the prescription of art. 927 of the New Civil Procedure Code, as a legal and procedural manner that can promote uniformity of interpretation, because it requires that judges and courts to comply with the decisions of the Superior Courts. Constitutional rule of tax jurisdiction arises as definition and interpretation vector of legal precedent on tax matters, because according to the National Constitution of 1988, which articulates a kind of Brazilian constitutional system of skills, there is a set of constitutional rules governing the distribution of tax revenues (arts. 145, 148, 149, 149-A, 153, 154, 155, 156 and 195) with the allocation of administrative and legislative powers (arts. 21, 22, 23, 24, 25, 30 and 32). This correlation is important because of regulatory innovations introduced by the New Civil Procedure Code, in particular the impacts of the prescription of art. 927, according to which judges and courts will abide by the decisions of the Supreme Court in concentrated control of constitutionality, the statements of binding precedent, the judgments on competence-taking incident or resolution of repetitive demands and trial of extraordinary resources and special repetitive utterances of the precedents of the Supreme Court in constitutional matters and the Superior Court of Justice in infra matter and the orientation of the plenary or special body to which they are linked. The objective of this study is to demonstrate that you can only set a legal precedent in tax matters, from which prescribes the art. 927 of the New Civil Procedure Code, if the court has, according to the Republican Constitution, the power to decide, ultimately, the legal and tax matters discussed in concrete case, object of the tax process